IEEE Guide for Aeolian Vibration Field Measurement of Overhead Conductors (IEEE, 2006)
Current practices related to field measurements of aeolian vibration of overhead conductors are covered in this guide.
Keywords: Electric conductors -- Congresses.; Overhead electric lines.; Overhead electric lines -- Vibration.; Vibration -- Measurement.